"Transformasi Model Pengambilan Keputusan Konsumen Pendidikan Islam di Era Digital: Dampak Teknologi, Kontroversi Perubahan Sistem Pendidikan, dan Studi Kasus di SMA Darul Mukhlashin" - M.HAFIDUDDIN (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study examines the impact of digital technology, specifically social media, on consumer decision-making in the context of Islamic education at a private school in Probolinggo, Indonesia. As access to information increasingly shifts to digital platforms, it is essential to understand how this change influences the decisions of parents and students when selecting an Islamic educational institution. Social media platforms, such as Instagram and Facebook, have become key tools for schools to engage with prospective students and their families. However, the depth and accuracy of the information provided through these platforms play a crucial role in the decision-making process. Using a qualitative approach and case study methodology, the research collected data through in-depth interviews and observations of the school’s social media presence. The findings reveal that social media significantly influences decision-making by providing easy access to information about school activities, values, and student life. While social media is effective in attracting initial interest, many parents and students still seek more detailed information, particularly about academic achievements and school facilities, before finalizing their decision. The study concludes that while social media is a valuable tool for engagement, it must be complemented by additional communication channels, such as school visits or comprehensive websites, to offer a fuller understanding of the institution. This research provides insights into how schools can enhance their digital presence to facilitate more informed decision-making